Two-dimensional measurements of receptor-ligand interactions - Zheng, Songjie; Zou, Min; Shao, Yingfeng; Wu, Huaping; Wu, Helong; Wang, Xiaohuan (Frontiers in Molecular Biosciences, 2023)
Gaining insight into the two-dimensional receptor-ligand interactions, which play a significant role in various pivotal biological processes such as immune response and cancer metastasis, will deepen our understanding of numerous physiological and pathological mechanisms and contribute to biomedical applications and drug design. A central issue involved is how to measure the in situ receptor-ligand binding kinetics. Here, we review several representative mechanical-based and fluorescence-based methods, and briefly discuss the strengths and weaknesses for each method. In addition, we emphasize the great importance of the combination of experimental and computational methods in studying the receptor-ligand interactions, and further studies should focus on the synergistic development of experimental and computational methods.